(untitled) (The Journal of Geography Education in Africa, 2021)
Keith Beavon was said to be ‘a born teacher’. Adding to his innate teaching ability were benefits from his unusual school education. As the son of a magistrate, he moved often and attended eight different schools! He was certainly exposed to a wide variety of teaching styles. But why did he choose Geography specifically?